Synthesis of fused tricyclic amines unsubstituted at the ring-junction positions by a cascade condensation, cyclization, cycloaddition then decarbonylation strategy - Coldham, Iain; Burrell, Adam J. M.; Guerrand, Hélène D. S.; Watson, Luke; Martin, Nathaniel G.; Oram, Niall (Beilstein Journal of Organic Chemistry, 2012)
Heating aldehydes that contain a protected hydroxymethyl group, a tethered alkyl chloride and a tethered alkenyl group at the α-position of the aldehyde with an amine sets up a cascade (tandem) reaction sequence involving condensation to an intermediate imine, then cyclization and formation of an intermediate azomethine ylide and then intramolecular dipolar cycloaddition. The fused tricyclic products are formed with complete or very high stereochemical control. The hydroxymethyl group was converted into an aldehyde – which could be removed to give the tricyclic amine products that are unsubstituted at the ring junction positions – or was converted into an alkene, which allowed the formation of the core ring system of the alkaloids scandine and meloscine.
Keywords: alkaloid; azomethine ylide; dipolar cycloaddition; heterocycle; tricyclic